A interferência das variáveis sexo e tempo de prática na motivação de atletas de handebol - FERREIRA FILHO, Arlei Roberto Caetano (2019)
The present study aims to analyze the interference of gender and practice time variables in the motivation of handball athletes. Participating in this study were 53 athletes of the adult category, 30 athletes in the male suit and 23 athletes in the female suit, belonging to 4 teams participating in the Paraense Handball Championship - Northeastern Conference, these teams being in the state of Pará. is 25.55 ± 5.42 years and the practice time in the modality is 10.79 ± 5.37 years. For the data collection, the questionnaire Motivation in Sports (EME-BR) validated by researchers from the Laboratory of Sports Psychology of the Federal University of Minas Gerais was used. Participants also completed a socio-demographic questionnaire with information such as age, gender, time of practice in the modality and time of federation. The results showed that male and female athletes did not present significant differences for the intrinsic, extrinsic and demotivation motivations, and did not obtain the values of (p <0.05) for the motivation dimensions. The athletes participating in the research did not present interference from the variables gender and time of practice. Thus, even the tournament being the most important in the state of Pará, allowing the teams the title of best team in the state, and providing athletes with individual and collective experiences, athletes of both sexes did not present significant differences among the fluctuating motivational.